1998
DOI: 10.1038/24808
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous ordering of bimodal ensembles of nanoscopic gold clusters

Abstract: Nature © Macmillan Publishers Ltd 19988 letters to nature 444 NATURE | VOL 396 | 3 DECEMBER 1998 | www.nature.com orbital occupied at each V 3+ site and the second electron occupying, respectively, the d xz and d yz orbitals in two sublattices as shown in Fig. 4. According to the Goodenough±Kanamori rules 14 , this orbital occupation naturally leads to the G-type antiferromagnetism 11 . A similar result was also obtained by band-structure calculation 15 . From Fig. 1, we see that the ferromagnetic component is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
550
0
5

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 719 publications
(564 citation statements)
references
References 29 publications
9
550
0
5
Order By: Relevance
“…Only one or two structures grow to larger length scales (,10 6 -10 8 particles). BNSLs with many particles per unit cell (for example, AB 4 , AB 5 , AB 6 , AB 13 ) might form when both charged and neutral nanoparticles of type B are incorporated into the structures. The presence of differently charged nanoparticles in the colloidal solutions ( Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Only one or two structures grow to larger length scales (,10 6 -10 8 particles). BNSLs with many particles per unit cell (for example, AB 4 , AB 5 , AB 6 , AB 13 ) might form when both charged and neutral nanoparticles of type B are incorporated into the structures. The presence of differently charged nanoparticles in the colloidal solutions ( Fig.…”
mentioning
confidence: 99%
“…Bacteria 1 , macromolecules 2 and nanoparticles 3 can self-assemble, generating ordered structures with a precision that challenges current lithographic techniques. The assembly of nanoparticles of two different materials into a binary nanoparticle superlattice (BNSL) [3][4][5][6][7] can provide a general and inexpensive path to a large variety of materials (metamaterials) with precisely controlled chemical composition and tight placement of the components. Maximization of the nanoparticle packing density has been proposed as the driving force for BNSL formation 3,8,9 , and only a few BNSL structures have been predicted to be thermodynamically stable.…”
mentioning
confidence: 99%
“…In general, feature sizes 30 -300 nm and larger are routinely produced by electron-beam and photolithography techniques, respectively. Important progress has been made over the past few years in the preparation of ordered ensembles of metal and semiconductor nanocrystals to fabricate feature size less than 30 nm [1,2]. Devices fabricated entirely from polymers are now available, opening up the possibility of adapting polymer processing technologies to fabricate inexpensive, large-area devices using non-lithographic techniques [3,4].…”
mentioning
confidence: 99%
“…While previous approaches for metal aerogels were based on the modification of oxide-based aerogels with metal nanoparticles for obtaining highly catalytically active materials (Pajonk 1997;Hüsing & Schubert 1998;Campbell 2004;Jiang & Gao 2006;Vallribera & Molins 2008), with this approach the resulting highly porous macroscopic monoliths are completely non-supportedly built only from metal nanoparticles. Owing to their large surface and the lack of supporting material, these monoliths have an enormous advantage in comparison with previously reported superstructural materials from metal nanoparticles such as mesoporous platinum-carbon composites (Warren et al 2008), gold nanoparticles interlinked with dithiols (Joseph et al 2009), nanochains of hybrid palladium-lipid nanospheres as reported by Zhou et al (2009), electrocatalytically active nanoporous platinum aggregates as reported by Viswanath et al (2009), foams (Banhart 2001;Schroers et al 2003) and highly ordered two-dimensional and three-dimensional supercrystals (Kiely et al 1998;Rabani et al 2003;Fan et al 2004;Kalsin et al 2006;Shevchenko et al 2006), artificial opals (Lu et al 2005a,b), fungal templated (Bigall et al 2008a) or even non-supported assemblies of dithiol-cross-linked supraspheres (Klajn et al 2007(Klajn et al , 2008. The averaged densities of the novel metal nanoparticle hydro-and aerogels were determined to be 0.016 g cm −3 corresponding to approximately 1/1000th of the averaged bulk density of gold and silver, which is two orders of magnitude lower than that of the reported foams.…”
Section: Hydrogels and Aerogels From Noble Metal Nanoparticlesmentioning
confidence: 99%